2006
DOI: 10.1111/j.1365-2915.2006.00640.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temephos and temperature onWolbachiaload and life history traits ofAedes albopictus

Abstract: Maternally inherited Wolbachia (gram-negative bacteria) often affect the reproductive fitness of their arthropod hosts and may cause cytoplasmic incompatibility (CI). Comparing Wolbachia-infected and uninfected strains of the mosquito Aedes albopictus (Skuse) (Diptera: Culicidae), we assessed the effects on fitness of two stressors: temperature elevation (25 degrees C vs. 37 degrees C) and exposure to temephos insecticide (concentration range 0.0017-0.0167 mg/L) during larval development. Fitness was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 37 publications
3
18
0
1
Order By: Relevance
“…Consistent with this, the titer of wRi in D. simulans embryos is approximately sixfold greater than wMel in D. melanogaster embryos (144). This elevated wRi concentration may also aid the nuclear-association transmission strategy by buffering detrimental influences on Wolbachia titer such as adverse changes in host crowding, host age, host genetic background, and the availability of food (25,46,66,76,78,94,99,106,115,144,151 (9). Studies of Wolbachia localization patterns as related to different host organisms will shed light on these fascinating issues in the future.…”
Section: How Wolbachia Localization Relates To Transmissionsupporting
confidence: 50%
“…Consistent with this, the titer of wRi in D. simulans embryos is approximately sixfold greater than wMel in D. melanogaster embryos (144). This elevated wRi concentration may also aid the nuclear-association transmission strategy by buffering detrimental influences on Wolbachia titer such as adverse changes in host crowding, host age, host genetic background, and the availability of food (25,46,66,76,78,94,99,106,115,144,151 (9). Studies of Wolbachia localization patterns as related to different host organisms will shed light on these fascinating issues in the future.…”
Section: How Wolbachia Localization Relates To Transmissionsupporting
confidence: 50%
“…aegypti responded differently to challenge by heat stress and UV-radiation. Temperature affects biochemical, physiological, and behavioral processes in mosquitoes (Narang and Narang 1975, Beach et al 1989, Mahmood and Crans 1997, Wiwatanaratanabutr and Kittayapong 2006. In our study, the inßuence of heat stress on the expression of the AeaCytC gene was shown to be higher in 2-d-old mosquitoes than in 9-d-old mosquitoes.…”
Section: Discussionsupporting
confidence: 45%
“…Wolbachia density probably influences the rate of maternal inheritance, resulting in different CI penetrance. CI intensity has been shown to be affected by several factors such as Wolbachia strain, host species, temperature and rearing density (Boyle et al, Hoffmann et al, 1996;Clancy and Hoffmann, 1998;Wiwatanaratanabutr and Kittayapong, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Real-time quantitative PCR is an accurate, sensitive, and reliable technique which can detect and estimate Wolbachia density in various host species. There have been several studies of Wolbachia density in insects that used this method (Kondo et al, 2002;McGraw et al, 2002;Wiwatanaratanabutr and Kittayapong, 2006). The aim of this study was to improve our understanding of the relationships between Wolbachia density and host species by comparing the relative density of Wolbachia in each developmental stage of mosquito under different host rearing conditions in terms of crowding effects and temperature effects.…”
Section: Introductionmentioning
confidence: 99%